Exploring the Customer Journey of Voice Commerce: A Research Agenda - Böhm, Eva; Eggert, Andreas; Garnefeld, Ina; Holzmüller, Hartmut H.; Schaefers, Tobias; Steinhoff, Lena; Woisetschläger, David M. (Journal of Service Management Research)
Voice commerce creates unprecedented opportunities for consumers and vendor firms to interact, engage, and relate. With artificial intelligence-powered voice assistants, consumers can make technology-mediated purchases without using their tactile senses, which represents a new space for commercial interactions. Drawing on the customer journey as an organizing framework, this article proposes a structured research agenda, in an attempt to shed light on the bright side effects of voice commerce while also acknowledging concerns for consumer protection and society in general. Voice assistants can enhance every stage of the purchase journey, yet their use might have negative consequences for customer relationships. In the prepurchase stage, voice assistants can act as information curators or manipulators. In the purchase stage, voice assistants can adopt roles as shopping concierges or impediments. In the postpurchase and usage stage, voice assistants can become trusted relationship partners or hostile intruders in consumers’ lives.
Keywords: General Agricultural and Biological Sciences

Customer Engagement in International Markets - Steinhoff, Lena; Liu, Juanyi (Sunny); Li, Xiaoling; Palmatier, Robert W. (Journal of International Marketing)
Relationship marketing managers around the world actively try to stimulate customer engagement because of its performance-enhancing effects. Research insights into how to engage customers, such that they voluntarily contribute their resources to support companies’ marketing efforts, almost exclusively pertain to individual, domestic markets. However, the prerequisites of customer engagement strategies naturally differ across country-specific market environments. Therefore, the authors develop a conceptual, comprehensive battery of cultural, institutional, societal, and economic country-level contingency factors (CISE indicators) as well as between-country psychic distances on those indicators. A set of 11 high-level research propositions aims to enhance marketing researchers’ and managers’ understanding of the contingencies of international customer engagement strategy effectiveness and customer engagement's performance ramifications. The analysis reflects the richness and complexity of potential contingency effects across the four CISE categories and encourages empirical research on their separate and joint effects.
Keywords: Marketing; Business and International Management

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Chemotaxis and cross-diffusion models in complex environments: Models and analytic problems toward a multiscale vision. - Bellomo, Nicolas; Outada, Nisrine; Soler, Juan; Tao, Youshan; Winkler, Michael (Mathematical Models & Methods in Applied Sciences)

Global existence in reaction-diffusion systems with mass control under relaxed assumptions merely referring to cross-absorptiva effects. - Lankeit, Johannes; Winkler, Michael (Journal of Evolution Equations)

A double critical mass phenomenon in a no-flux-Dirichlet Keller-Segel system. - Fuhrmann, Jan; Lankeit, Johannes; Winkler, Michael (Journal de Mathématiques Pures et Appliquées)

A smallness condition ensuring boundedness in a two-dimensional chemotaxis-Navier-Stokes system involving Dirichlet boundary conditions for the signal. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Acta Mathematica Sinica (English Series))

Global mass-preserving solutions to a chemotaxis-fluid model involving Dirichlet boundary conditions for the signal. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Analysis and Applications)

Social/dialogical roles of social robots in supporting children’s learning of language and literacy—A review and analysis of innovative roles - Rohlfing, Katharina; Altvater-Mackensen, Nicole; Caruana, Nathan; van den Berghe, Rianne; Bruno, Barbara; Tolksdorf, Nils Frederik; Hanulíková, Adriana (Frontiers in Robotics and AI)
One of the many purposes for which social robots are designed is education, and there have been many attempts to systematize their potential in this field. What these attempts have in common is the recognition that learning can be supported in a variety of ways because a learner can be engaged in different activities that foster learning. Up to now, three roles have been proposed when designing these activities for robots: as a teacher or tutor, a learning peer, or a novice. Current research proposes that deciding in favor of one role over another depends on the content or preferred pedagogical form. However, the design of activities changes not only the content of learning, but also the nature of a human–robot social relationship. This is particularly important in language acquisition, which has been recognized as a social endeavor. The following review aims to specify the differences in human–robot social relationships when children learn language through interacting with a social robot. After proposing categories for comparing these different relationships, we review established and more specific, innovative roles that a robot can play in language-learning scenarios. This follows Mead’s (1946) theoretical approach proposing that social roles are performed in interactive acts. These acts are crucial for learning, because not only can they shape the social environment of learning but also engage the learner to different degrees. We specify the degree of engagement by referring to Chi’s (2009) progression of learning activities that range from active, constructive, toward interactive with the latter fostering deeper learning. Taken together, this approach enables us to compare and evaluate different human–robot social relationships that arise when applying a robot in a particular social role.
Keywords: Artificial Intelligence; Computer Science Applications

Developmental Paths of Pointing for Various Motives in Infants with and without Language Delay - Rohlfing, Katharina J.; Lüke, Carina; Liszkowski, Ulf; Ritterfeld, Ute; Grimminger, Angela (International Journal of Environmental Research and Public Health)
Pointing is one of the first conventional means of communication and infants have various motives for engaging in it such as imperative, declarative, or informative. Little is known about the developmental paths of producing and understanding these different motives. In our longitudinal study (N = 58) during the second year of life, we experimentally elicited infants’ pointing production and comprehension in various settings and under pragmatically valid conditions. We followed two steps in our analyses and assessed the occurrence of canonical index-finger pointing for different motives and the engagement in an ongoing interaction in pursuit of a joint goal revealed by frequency and multimodal utterances. For understanding the developmental paths, we compared two groups: typically developing infants (TD) and infants who have been assessed as having delayed language development (LD). Results showed that the developmental paths differed according to the various motives. When comparing the two groups, for all motives, LD infants produced index-finger pointing 2 months later than TD infants. For the engagement, although the pattern was less consistent across settings, the frequency of pointing was comparable in both groups, but infants with LD used less canonical forms of pointing and made fewer multimodal contributions than TD children.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Expression of CXCR4 on CD4+ T cells predicts body composition parameters in female adolescents with anorexia nervosa. - Freff, J; Bröker, L; Leite Dantas, R; Schwarte, K; Bühlmeier, J; Kraft, I; Hinney, A; Buhlmann, U; Arolt, V; Dannlowski, U; Romer, G; Baune, BT; et al. (Front Psychiatry)

Reinforcement Learning-Based Deep Q Direct Torque Control with Adaptable Switching Frequency Towards Six-Step Operation of Permanent Magnet Synchronous Motors - Haucke-Korber, Barnabas; Schenke, Maximilian; Wallscheid, Oliver (IKMT 2022; 13. GMM/ETG-Symposium)

Participative human-factor evaluation in the context of digital work (re-)design - Schumacher, Jan-Philip; Depenbusch, Sarah; Straatmann, Tammo; Bender, Elena; Schaper, Niclas; Hamborg, Kai-Christoph (Work)
BACKGROUND: Challenged by digital transformation, organizations increasingly integrate information and communication technologies into work designs. Often focal points of such digital reengineering initiatives are technical and economic aspects. Yet, as integration of new technologies affects how employee work and interact, there is a need to evaluate human-centered criteria (human-factor evaluation), optimally by involving employees as situational experts. OBJECTIVE: The present study develops an integrative and persona-based evaluation approach of human-centered criteria for application in participative digital (re-)design of work to support the joint optimization of the technical and social system. METHODS: Drawing on methods from usability evaluation, a persona-based approach is developed to facilitate comprehension and application of human-centered evaluation by employees. To that end, human-centered criteria from existing evaluation models are systemized with specific reference to digital transformation of work processes. The developed approach is tested in pilot runs of three German small and medium-sized enterprises (SMEs). RESULTS: The initial overview shows a divergence of specific human-centered criteria at the detailed level. Simultaneously, a high convergence is found for overarching dimensions and categories. The Integrative Socio-Digital Evaluation Model (ISDEM) is developed to balance complexity and abstraction of criteria. The derived persona-based approach (persISDEM) shows a good applicability in the pilot runs. CONCLUSIONS: The present study provides an amendment to existing work design approaches with an emphasis on employee participation, enabling organizations to foster employees’ comprehension and motivation to engage in evaluations of digital (re-)design of work and to create motivating and healthy jobs for successful digital transformation.
Keywords: Public Health; Environmental and Occupational Health; Rehabilitation

Multiplikative Beziehungen erkennen und nutzen – Initiierung von Lernprozessen durch Entdeckervideos - Häsel-Weide, Uta; Wienhues, Inga; Kordes, L. (Digitale Medien und Heterogenität – Chancen und Herausforderungen für die Mathematikdidaktik)

Qualitätssicherung im bildungswissenschaftlichen Studium – methodologische Überlegungen. - Seifert, Andreas; Watson, Christina (DGPs-Tagung „View on of Science“)

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (ICL2022 – 25th International Conference on Interactive Collaborative Learning 27–30 September 2022, Hilton Park Vienna, Austria)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Vielfalt stärken im naturwissenschaftlich-technischen Sachunterricht – Mehrperspektivische Sichtweisen zur Nutzung sprachlicher und kultureller Heterogenität im Sachunterricht der Grundschule und in der sachunterrichtsdidaktischen Lehrer*innenausbildung - Blumberg, Eva; Brenke, Laurien; Schürmann, Michelle; Gövert, André (Das Projekt "Vielfalt stärken")

Sachunterricht lehren in Zeiten der Pandemie – Eine Online-Befragung zu den Auswirkungen der digitalen Lehre auf den Materialeinsatz in der sachunterrichtsdidaktischen Hochschulausbildung - Thonemann, Lisa; Deutschen, Katrin; Lakemeyer, Jana Marie; Reh, Anne; Blumberg, Eva (GDSU-Journal)

Sachunterricht begründet planen – Das Prozessmodell Generativer Unterrichtsplanung Sachunterricht (GUS) - Tänzer, Sandra; Lauterbach, Roland; Blumberg, Eva; Grittner, Frauke; Lange, Jochen; Schomaker, Claudia (GDSU-Journal)

Potential kernels for radial Dunkl Laplacians - Graczyk, P.; Luks, Tomasz; Sawyer, P. (Canadian Journal of Mathematics)

Effects of the composition of pre-service teacher teams on primary school students’ competencies in (non-)inclusive science lessons. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Digitales Sachunterrichtsstudium in der Corona-Krise – Eine empirische Evaluationsstudie zur Rezeption des Unterstützungsangebots des Paderborner Lernzentrums „Sachunterrichtstreff“ bei Sachunterrichtsstudierenden im Grund- und Förderschullehramt - Deppe, Franziska; Reh, Anne; Blumberg, Eva (GDSU-Journal)

Effects on primary and secondary school students’ academic out-of-school learning experiences in Science Technology Engineering Mathematics (STEM) education. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Schulze, Jan Roland; Crummenerl, Lena Luise; Sicking, Annika; Temmen, Katrin; Blumberg, Eva

Monopolbildung im Zuge der Globalisierung und Digitalisierung der GAFA-Unternehmen (Google, Amazon, Facebook, Apple) - eine wettbewerbspolitische Analyse - Sarsar, Abdelmajid

Kartelle und technischen Absprachen zur Forschung und Entwicklung - Eine wettbewerbspolitische Analyse anhand der Automobilindustrie - Bas, Mikail

Blockchain Technology and the Internet of Thing-Risks and Chances for Supply Chains - Vikue, Baribuma Lucy

Die Fusion von Kaiser's Tengelmann und EDEKA - eine wettbewerbspolitische Analyse - Taskin, Ibrahim

Essen in Kindertageseinrichtungen. Orientierungsmuster von Fachkräften zwischen Anpassung und Ermöglichung - Klein, Alexandra; Landhäußer, Sandra (Soziale Passagen)
Immer mehr Kinder besuchen täglich pädagogische Einrichtungen und verbringen dort zunehmend mehr Zeit; dies führt dazu, dass sie auch vermehrt in pädagogischen Einrichtungen essen. Als Qualitätsmerkmal von Kindertageseinrichtungen wird dabei zunehmend das Thema Essen als gesunde Ernährung zentral. Gleichzeitig liegen bislang erst wenige Studien vor, die auch die Beteiligungs- und Selbstbestimmungsmöglichkeiten von Kindern beim Essen im Alltag der Kindertageseinrichtung betrachten. Auf der empirischen Basis der Frankfurter Kinderbefragung 2018 fragt der vorliegende Beitrag danach, mit welchen kollektiven Orientierungsmustern pädagogische Fachkräfte in Kindertageseinrichtungen die Mahlzeiten gestalten und welche Rolle sie den beteiligten Akteur*innen darin zuweisen. Während in den Gruppendiskussionen einerseits disparate Orientierungen an Ernährungserziehung und Ernährungsbildung sichtbar werden, eint sie andererseits, dass den Kindern selbst kaum substanzielle Einflussmöglichkeiten auf die soziale Gestaltung der Mahlzeit eröffnet werden.
Keywords: Ernährung Mahlzeiten Gruppendiskussion Dokumentarische Methode Beteiligung

Alternative Wahrnehmungen der Welt gelten lassen? Herausforderungen eines rassismuskritischen Unterrichts in der Erzieher_innenausbildung - Kuhn, Melanie; Landhäußer, Sandra (Sozial Extra)
Rassismus kommt als Lerninhalt in den Lehrplänen für die Ausbildung von Erzieher_innen kaum vor. Eine sensible und nicht moralisierende Thematisierung von Rassismus im Unterricht ist so wichtig wie herausfordernd. Die Vermittlung von rassismuskritischem Wissen zum einen und die Selbstpositionierungen der Lehrkräfte zum anderen können dazu beitragen, dass Rassismus nicht unbeabsichtigt bagatellisiert und relativiert wird.
Keywords: Differenz Rassismuskritik Erzieher_innenausbildung Fachschule

Care! Zum Verhältnis von Sorge und Sozialer Arbeit
Der Band hat zum Ziel verschiedene Dimensionen von Care ins Verhältnis zur Sozialen Arbeit zu setzen und diese wechselseitigen Verknüpfungen kritisch zu beleuchten. Die Relevanz einer solchen Verhältnisbestimmung ergibt sich aus der Beobachtung, dass Care im Kontext der Sozialen Arbeit bislang kaum explizit behandelt wird. Es werden grundsätzliche Konfliktlinien beleuchtet, Einblicke in exemplarische Felder gegeben sowie bereits existierende Alternativen, Möglichkeiten für Solidarisierung und soziale Innovationen aufgezeigt.
Keywords: Erhik/Sozialethik; Politik; Recht; Staat; Verwaltung; Parteien; Sozial/Politik; Staat. Recht; Sozialarbeit; Sozialethik

Following carbon condensation by in situ TEM: towards a rational understanding of the processes in the synthesis of nitrogen-doped carbonaceous materials - Piankova, Diana; Kossmann, Janina; Zschiesche, Hannes; Antonietti, Markus; Lopez Salas, Nieves; Tarakina, Nadezda V. (Journal of Materials Chemistry A)
In situ TEM heating experiments combined with extensive chemical, structural and sorption analysis reveal the nanoscale mechanism of porosity formation in carbonaceous materials obtained directly from molecular precursors.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Modulating between 2e− and 4e− pathways in the oxygen reduction reaction with laser-synthesized iron oxide-grafted nitrogen-doped carbon - Wang, Huize; Jerigova, Maria; Hou, Jing; Tarakina, Nadezda V.; Delacroix, Simon; Lopez Salas, Nieves; Strauss, Volker (Journal of Materials Chemistry A)
Laser patterning of different precursor mixtures allows modulating the selectivity of iron oxide supported on N-doped carbons for ORR electrocatalysis.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; Lopez Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian; Kühne, Thomas D.; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

C 1 N 1 Thin Films from Guanine Decomposition Fragments - Jerigová, Mária; Heske, Julian; Kühne, ThomasD.; Tian, Zhihong; Tovar, Michael; Odziomek, Mateusz; Lopez Salas, Nieves (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Wissenstransfer aus kulturwissenschaftlicher Perspektive. Konturen, Konzepte und Grenzen der Transferidee - Meier, Rebecca; Harmening, Anda-Lisa Martha Josephine Anna; Leinfellner, Stefanie (Wissenstransfer. Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Engaging with self-tracking applications: how do users respond to their performance data? - Constantiou, Ioanna; Mukkamala, Alivelu; Sjöklint, Mimmi; Trier, Matthias (European Journal of Information Systems)
Keywords: Library and Information Sciences; Information Systems; Self-Tracking; User Behaviour; Discontinuance

Engaging with self-tracking applications: how do users respond to their performance data? - Constantiou, Ioanna; Mukkamala, Alivelu; Sjöklint, Mimmi; Trier, Matthias (European Journal of Information Systems)
Keywords: Library and Information Sciences; Information Systems

The Black Box of Social Commerce Platforms - A Closer Look at Users’ Activities - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Wirtschaftsinformatik 2022 Proceedings)

Hier wie dort? Ein Vergleich der Tätigkeits- und Kooperationsprofile von Schulbegleitungen an inklusiven Gesamtschulen und Förderschulen in Nordrhein-Westfalen - Kullmann, Harry; Globisch, Eva-Luisa; Heister, Nicolas (Wege der Kooperation im Kontext inklusiver Bildung)

Inklusionsbezogenes Potenzial der kulturellen Bildung am Beispiel des Darstellendes Spiels/Theaters in der Schule - Kullmann, Harry; Stieling, Helena (Kulturelle Bildung)

Rate splitting in MIMO RIS-assisted systems with hardware impairments and improper signaling - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard (IEEE Transactions on Vehicular Technology)

Multi-Task fMRI Data Fusion Using IVA and PARAFAC2 - Lehmann, Isabell; Acar, Evrim; Hasija, Tanuj; Akhonda, M.A.B.S.; Calhoun, Vince D.; Schreier, Peter J.; Adali, Tülay (Proc. IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Narrative Schemaaktivierung und vorschulischer Erzählerwerb – eine gebrauchsbasierte Analyse über die Verwendung narrativer Konstruktionen zur Gestaltung einer temporalen Handlungsabfolge - Uhl, Benjamin; Drepper, Laura (Temporalität – empirische Zugänge zum Erwerb von Zeitlichkeit)

Tempuserwerb zwischen Mündlichkeit und Schriftlichkeit – Empirische Ergebnisse zum vorschulischen Erwerb von implizitem Handlungswissen über die Tempusverwendung in narrativen Kontexten. - Drepper, Laura (Temporalität – empirische Zugänge zum Erwerb von Zeitlichkeit)

Journal of the History of Women Philosophers and Scientists
Founded by Ruth Edith Hagengruber and Mary Ellen Waithe, the Journal of the History of Women Philosophers and Scientists (JHWP) is the world's first journal dedicated to restoring and discussing the history of the texts written by and about women philosophers. The Journal of the History of Women Philosophers and Scientists seeks to integrate women’s intellectual heritage into the canon of philosophy, the humanities, and the natural and social sciences. It publishes peer-reviewed articles about women’s contributions to these disciplines. The time period investigated by articles in the Journal of the History of Women Philosophers and Scientists ranges from 2200 BCE to the 20th century CE in both the Western and non-Western world. The Journal of the History of Women Philosophers and Scientists publishes biannually thematic issues on particular philosophical topics. Leading philosophers from all over the world in the corresponding fields serve as guest editors of the relevant issue. Each issue is a collected anthology of continuing interest. The Journal of the History of Women Philosophers and Scientists understands itself as a renewal of philosophy and a critical instrument to the hitherto studied traditions.

Out of the Box – into the Green and the Blue: A Plea for a Post-humanist Information Society - Hagengruber, Ruth Edith (The Green and the Blue)

Reply to a Reply: Knowledge in the Digitized World: The Third Knowledge Dimension - Hagengruber, Ruth Edith (The Green and the Blue. Digital Politics in Philosophical Discussion)

Üben, Üben, Üben – Ein Dreiergespräch über die religions- und philosophiedidaktische Grundfrage nach der Ambiguität der Praxis als Ort der Wahrheit - Schroeter-Wittke, Harald; Kamcili-Yildiz, Naciye; Berner-Zumpf, Daniela (Zeitschrift für Pädagogik und Theologie)

Mind the Gap: Grund-Riss einer konfessionalen Religionspädagogik. Antonia Lüdtke: Confessional Gap. Konfessionalität und Religionsunterricht denken, Kohlhammer Verlag: Stuttgart 2020, 440 S. - Schroeter-Wittke, Harald (Praktische Theologie)